Implementasi Matode Weighted Product Dalam Penentuan Aplikasi Tatap Muka Pembelajaran Daring Dimasa Pandemi Covid-19 - Zega, Serta Kurniawan; Zai, Viktor Frank; Bu'ulolo, Efori (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The covid-19 pandemic as we have experienced lately has overwhelmed the community so that activities in various fields are hampered, one of which is in the field of education where the government shifts face-to-face learning to learning which can be done with various visual media such as Classroom, Zoom, Google Meet, E-learning and so on. Due to the large number of media that can be used for learning, a determination is needed to choose a face-to-face online learning application. In the determination, a system is needed, namely a decision support system where this system can provide efficient and objective decisions based on predetermined methods and data. , in this study determine the WP (Weighted Product) method as a decision-making tool which is part of the DSS method. And by setting 5 alternatives or applications that are calculated and determined the 5 criteria that are used as requirements in order to produce the right decision. So from the problems above, this study was made which discusses the implementation of the WP method in determining the application used for face-to-face during online learning during the covid-19 pandemic. Based on the implementation of this method, a face-to-face online learning application is produced, namely the A3 alternative, namely Elearning with a preference value of 0.341.